2016
DOI: 10.1162/rest_a_00551
|View full text |Cite
|
Sign up to set email alerts
|

Globalization and Wage Polarization

Abstract: In the 1980s and 1990s, the US labour market experiences a remarkable polarization along with fast technological catch-up, as Europe and Japan improve their global innovation performance. Is foreign technological convergence an important source of wage polarization? To answer this question, we build a multi-country Schumpeterian growth model with heterogeneous workers, endogenous skill formation and occupational choice.We show that convergence produces polarization through business stealing and increasing comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…Although, the across‐sector average for Europe is fairly constant, in some innovation‐intensive industries Europe's share of global R&D grows substantially in this period. Similar trends are observable for the distribution of patent counts and citations (Cozzi and Impullitti, ; Akcigit et al., ). This suggests that US global technological leadership was increasingly challenged by foreign firms during the years of increasing wage inequality.…”
Section: Introductionsupporting
confidence: 66%
See 3 more Smart Citations
“…Although, the across‐sector average for Europe is fairly constant, in some innovation‐intensive industries Europe's share of global R&D grows substantially in this period. Similar trends are observable for the distribution of patent counts and citations (Cozzi and Impullitti, ; Akcigit et al., ). This suggests that US global technological leadership was increasingly challenged by foreign firms during the years of increasing wage inequality.…”
Section: Introductionsupporting
confidence: 66%
“…Figure provides a clear picture of convergence in global R&D efforts. Cozzi and Impullitti () and Akcigit et al (), show that a similar convergence path can be observed for innovation output, patents and its quality, patent citations.…”
Section: Stylized Factsmentioning
confidence: 55%
See 2 more Smart Citations
“…Part (b) of Proposition 7 shows that enhanced education technology in one country could lead to “vanishing middle class” of its trading partner. However, the reason for this to happen is not the commonly believed “import competition.” In Cozzi and Impullitti (), reduction in the technology gap results in polarization in the more advanced trading partner, because competition from less developed countries has a business‐stealing effect, reducing wages of production workers in the leading economy and making it harder for domestic firms to innovate, thus pushing them to devote more labor resources to innovation. This triggers an increase in the demand for skilled workers and the service workers (the lowest‐ability individuals), creating the polarization.…”
Section: Discussionmentioning
confidence: 99%